Parametric Selection and Optimization of Al-Mg-Mn-Zr-Er Alloy Weld Bead Geometry Welded by Laser Using the Aspect Ratio-Based Taguchi Method - Umoh, Akwaeno Uduak; Oke, Sunday Ayoola; Rajan, John; Oluwo, Adeyinka; Oyekeye, Manasseh Olusegun; Jose, Swaminathan; Aderibigbe, Samuel Bolaji; Odudare, Samson Oluwaseun (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2024)
At present, there is a continuous escalation of labour costs, material costs and other welding-related costs and stabilizing them is challenging. Therefore, optimization of the welding process is essential to stabilize the situation. In this article, an aspect ratio-based Taguchi method is proposed to control the operational performance of the laser welding process while welding the Al-Mg-Mn-Zr-Er alloy sheets. The direct parameters considered are the laser power (LP), welding speed (WS) and welding feed rate (WFR). The aspect ratios analyzed are LP/WS, LP/WFR, WS/LP, WS/WFR, WFR/LP and WFR/WS. The aspect ratios are introduced into the factor/level framework, and the results, transmitted as orthogonal arrays are changed to signal-to-noise ratios. The final results are the delta values, ranks and optimal parametric settings. The principal results indicate that for the LPWS and LP/WFR formulation, the optimal parametric setting is LP/WS1LP/WFR3, which is interpreted as 1.6 kWmin/m LP/WS and 0.35 kWmin/m of LP/WFR. The corresponding delta values are 3.875 and 2.6288 while the positions of 1st and 2nd were obtained by LP/WS and LP/WFR aspect ratios, respectively. It was established that the LP/WS, WS/WFR and WFR/LP are the most important aspect ratios for the laser welding of Al-Mg-Mn-Zr-Er alloy sheets. Therefore, prioritization in resource distribution should be given to these parameters according to their positions. This article serves as a source of information for welding decision-making.